Unravelling the impact of soil types on zinc, iron, and selenium concentrations in grains and straw of wheat/Amblyopyrum muticum and wheat/Triticum urartu doubled haploid lines - Guwela, Veronica F.; Broadley, Martin R.; Hawkesford, Malcolm J.; Maliro, Moses F. A.; Bokosi, James; Banda, Mike; Grewal, Surbhi; Wilson, Lolita; King, Julie (Frontiers in Agronomy, 2024)
The concentration of mineral nutrients in plants is associated with bioavailabilities of soil mineral nutrients, which are regulated by various soil physio-chemical properties. A pot experiment was conducted to investigate the effects of soil type on grain and straw zinc (Zn), iron (Fe) and selenium (Se) concentrations of wheat/Amblyopyrum muticum and wheat/Triticum urartu doubled haploid lines. A set of 42 treatments in a factorial combination with 21 genotypes and two soil types collected from Ngabu and Chitedze Research Stations in Malawi was laid in a randomised complete block design (RCBD) in three replicates. Soil analysis showed that the two soils had the same textural class (Sandy clay loam), but different mineral concentrations, pH levels and percentage organic matter. Grain and straw samples were analysed using inductively coupled plasma-mass spectrometry (ICP-MS). Analysis of variance revealed a ~two-fold higher Zn concentration in grains grown in low pH, high Zn soils (Chitedze soils) compared to grains grown in high pH, low Zn soils (Ngabu soils). Variation in grain Zn concentration was associated with the genotypes (p = 0002), soil type (p = <0.0001), and their interaction (p = 0.035). Grain Fe was 1.3-fold higher in low pH than in high pH soils, and it was influenced by genotypes (p = < 0.0001) and soil type (p = <0.0001). Grain Se was highly associated with soil type (p = <0.0001), and it was 30-fold higher in high pH than in low pH soils. Straw Zn was generally higher in plants grown in Chitedze soils than Ngabu soils, whilst straw Se was higher in plants grown in Ngabu soils than Chitedze soils. The findings demonstrate the significance of soil physio-chemical properties for mineral accumulation and distribution to plant parts, thus informing future breeding programs on important considerations on crop genetic biofortification with the three mineral elements.